2003
DOI: 10.1002/bjs.4103
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and physiological findings, and possible aetiological factors of rectal hyposensitivity

Abstract: Patients with RH display marked heterogeneity in terms of presenting symptoms. The exact causes of RH are unknown, but there is evidence to suggest that pelvic nerve injury and spinal trauma are possible aetiological factors. RH appears important in the aetiology of both constipation and faecal incontinence, and may be useful as a predictor of surgical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 38 publications
0
48
0
Order By: Relevance
“…Although manometry is part of routine clinical assessment in patients with significant defecation disorders, testing has not been standardized and limited information about normal values has been published. Investigations of healthy controls were typically performed in relatively young individuals with an often equal distribution of men and women [5,[11][12][13][14], contrasting with the demographics of patient groups, which are female predominant with an average age of about 50-60 years [12,[15][16][17][18][19][20]. Prior studies have demonstrated sexand age-related differences in anorectal physiology, thus raising questions about the utility of the known normal ranges in the interpretation of clinical test results [20][21][22].…”
Section: Introductionmentioning
confidence: 96%
“…Although manometry is part of routine clinical assessment in patients with significant defecation disorders, testing has not been standardized and limited information about normal values has been published. Investigations of healthy controls were typically performed in relatively young individuals with an often equal distribution of men and women [5,[11][12][13][14], contrasting with the demographics of patient groups, which are female predominant with an average age of about 50-60 years [12,[15][16][17][18][19][20]. Prior studies have demonstrated sexand age-related differences in anorectal physiology, thus raising questions about the utility of the known normal ranges in the interpretation of clinical test results [20][21][22].…”
Section: Introductionmentioning
confidence: 96%
“…The elevated volumes tolerated by the one third of patients with normal rectal diameters are thus likely to reflect impaired afferent nerve sensitivity, presumably with the proximal extension of the balloon on simple testing, 16 and such patients should be diagnosed more accurately with blunted rectal sensitivity, or rectal hyposensitivity. 17 By comparison, contrast studies to identify patients with IMR appeared to underestimate the prevalence of the condition, because one quarter of patients with increased rectal diameters during isobaric distention were found to have normal diameters during volumetric distention at evacuation proctography. Furthermore, four of six patients reported as having normal rectal diameters at DCBE were found to have increased diameters during isobaric distention.…”
Section: Discussionmentioning
confidence: 97%
“…For the purposes of inclusion in the study, IMR was defined on the basis of anorectal manometry, 11,12 when the maximum volume tolerated during latex balloon distention was elevated beyond the normal range (mean + 2 SD) for our unit, i.e., greater than 315 ml in males and 325 ml in females. 17 Accordingly, 30 consecutive patients (24 females; median age, 47 years, range, 25-72 years, P < 0.01 vs. HV) with IMR were studied. An additional 10 patients (8 women; median age, 39 years, range, 22-67 years) without evidence of IMR (normal MTV) (normal rectum, NR) were studied for comparison.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypersensitivity is now widely considered to play an important role in the development of symptoms in FGD, characterized by chronic abdominal pain [15]. Hyposensitivity of the rectum has been proposed as a relevant factor in the etiology of chronic constipation [16][17][18] and fecal incontinence [19,20]. Several research studies have been performed using the barostat technique to elucidate these hypotheses.…”
Section: Visceral Sensationmentioning
confidence: 99%